Exceptional atmospheric corrosion inhibition performance of super-hydrophobic films based on the self-propelled jumping behavior of water droplets - Peng Wang (Elsevier, 2021)
Super-hydrophobic surfaces have attracted much attention for their potential applications based on the lotus effect, especially in corrosion protection. However, the lotus effect has limited application given its high dependence on external forces, such as gravity and wind force. The self-propelled jumping behavior of water droplets, a newly found phenomenon over super-hydrophobic surfaces, would bring an alternative mechanism to atmospheric corrosion protection. Two different super-hydrophobic surfaces with a cone-shaped array microstructure and a flower-shaped hierarchical microstructure, respectively, were designed over copper substrate with an electrodeposition method. The dynamic growth and coalescence behavior of droplets were compared over the two super-hydrophobic surfaces. The cone-shaped array microstructure facilitates the self-jumping behavior of micro-droplets over the super-hydrophobic surface. In further, corrosion protection performance of the super-hydrophobic surfaces was examined after condensation in a simulated atmospheric environment. It was proven that the self-jumping behavior of micro-droplet helps remove the droplet over super-hydrophobic surfaces, thereby minimizing the likelihood of any subsequent corrosion behavior. This study demonstrates a novel corrosion protection mechanism for super-hydrophobic surfaces, and provides instructions for designing highly effective super-hydrophobic surfaces for corrosion protection.